Comparison of the ligase chain reaction with cell culture for the diagnosis of Chlamydia trachomatis infection in women. Issue 2 (February 1996) - Ridgway, G L; Mumtaz, G; Robinson, A J; Franchini, M; Carder, C; Burczak, J; Lee, H
Abstract : OBJECTIVE: To determine the sensitivity and specificity of ligase chain reaction (LCR) analysis of cervical and urine specimens from women compared with cell culture of cervical and urethral specimens for the diagnosis of genitourinary chlamydial infection. METHODS: Women (n = 624) attending the Genitourinary Medicine Clinic at University College London Hospitals, were enrolled. Patients who had received antibiotics within the previous two weeks were excluded. Specimens were obtained from the urethra and cervix for chlamydial culture, and from the cervix for LCR. A specimen of first void urine was also obtained for LCR. Discrepancies were resolved by direct immunofluorescence or a major outer membrane protein targeted LCR, or both. RESULTS: The prevalence of Chlamydia trachomatis in 600 patients, using an expanded standard of a positive cell culture or two confirmed positive non-culture tests, was 13.2% (79/600). Cervical culture detected 68.4% and urethral culture 62% of all positive results compared with 81% detected by cervical LCR and 69% by urine LCR. Cervical and urethral culture combined detected 87.3% whereas cervical and urine LCR combined detected 91.1% of positive cases. Specificity of LCR was 100% in the cervix and 99.8% in urine. CONCLUSION: This study demonstrates that LCR analysis of cervical and urine specimens is a reliable method for the diagnosis of chlamydial genital infection in women. However, the study also demonstrates that no single test will detect all chlamydial infections. Conventional non-culture tests and cell culture may grossly underestimate the prevalence of chlamydial infection. LCR analysis of a cervical specimen was superior to conventional cell culture without blind passage as a single test for diagnosing chlamydial infection in women, followed by LCR of a urine specimen.